Challenges and Coping Strategies of Multi-Grade Teachers (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
Multigrade classes in the Philippines are usually present in Elementary schools in remote areas where few students are in one-year level. Thus, teachers then handle multiple grade levels at a time. This study investigated the challenges and Coping strategies of Multigrade teachers in the western part of the Philippines. The researchers employed a Transcendental phenomenological method in this study. They gathered the data through one-to-one interviews of multigrade teachers who have been teaching for at least three years. Following the data analysis of Kleiman (2004), the results revealed that there were intrinsic, extrinsic, and system challenges experienced by these teachers. These challenges involved unpreparedness in teaching multigrade, low multigrade allowances, the experience of stress, language barrier, classroom management struggles, lack of resources, danger in going to stations, workload, absenteeism, lack of stakeholders’ support, and lack of trainings. However, they showed positivity in their work and applied the right coping strategies to lessen their burden. Among these coping strategies were praying, using the web, having time management, self-conditioning, developing plans, and doing research. The participants believed that handling Multigrade classes requires time, effort, and balance. Through these experiences, teachers learned to adjust and cope with the challenges they were facing. Thus, they became better educators.